2023
DOI: 10.1126/science.abn4705
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria metabolism sets the species-specific tempo of neuronal development

Abstract: Neuronal development in the human cerebral cortex is considerably prolonged compared to that of other mammals. We explored whether mitochondria influence the species-specific timing of cortical neuron maturation. By comparing human and mouse cortical neuronal maturation at high temporal and cell resolution, we found a slower mitochondria development in human cortical neurons compared with that in the mouse, together with lower mitochondria metabolic activity, particularly that of oxidative phosphorylation. Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 55 publications
5
97
0
Order By: Relevance
“…Across ExN clusters, isoforms of ENC1, ANKRD18CP, and RASD1 are enriched in ExN1, EnX2 and ExN3 cells, respectively (fig S10E-F). Moreover, vRG-ExN cells are defined by a majority of transcripts involved in mitochondrial metabolism, consistent with recent reports of the role of mitochondria in regulating neuronal maturation (75). Overall, the increased resolution in ExN and ExM cells obtained from isoform-based clustering matches the observed increase in isoform diversification in those cells (Fig.…”
Section: Novel Cell-types Uncovered From Isoform-level Clusteringsupporting
confidence: 90%
“…Across ExN clusters, isoforms of ENC1, ANKRD18CP, and RASD1 are enriched in ExN1, EnX2 and ExN3 cells, respectively (fig S10E-F). Moreover, vRG-ExN cells are defined by a majority of transcripts involved in mitochondrial metabolism, consistent with recent reports of the role of mitochondria in regulating neuronal maturation (75). Overall, the increased resolution in ExN and ExM cells obtained from isoform-based clustering matches the observed increase in isoform diversification in those cells (Fig.…”
Section: Novel Cell-types Uncovered From Isoform-level Clusteringsupporting
confidence: 90%
“…Human cortical projection neurons (CPNs) develop at their species-specific tempo when xenotransplanted in the fast-developing mouse cortex, pointing to cell-intrinsic mechanisms ( 913 ). While mitochondria metabolism was recently shown to regulate the species-specific tempo of global neuronal maturation ( 14 ), one outstanding molecular candidate for the specific timing of synaptic maturation is the SRGAP2 gene family ( 15 ). This family is composed of SRGAP2A, the ancestral gene shared by all mammals, and human-specific (HS) gene duplicates SRGAP2B, SRGAP2C and SRGAP2D, which emerged through segmental duplications during recent hominin evolution ( 16, 17 ).…”
Section: Main Textmentioning
confidence: 99%
“…It is widely recognized that properly functioning mitochondria are integral to normal brain development [ 6 , [19] , [20] , [21] ]. A new study has shown that different pace of neuronal development among species is attributable to differences in mitochondrial metabolism, especially oxidative phosphorylation [ 22 ]. Our findings provide a clearer view of mitochondrial respiration capacity in the developing brain.…”
Section: Discussionmentioning
confidence: 99%